Patent Foramen Ovale Closure: State of the Art - Joel P Giblett (Radcliffe Medical Media, 2020)
Patent foramen ovale (PFO) is a common abnormality affecting between 20% and 34% of the adult population. For most people, it is a benign finding; however, in some people, the PFO can open widely to enable paradoxical embolus to transit from the venous to arterial circulation, which is associated with stroke and systemic embolisation. Percutaneous closure of the PFO in patients with cryptogenic stroke has been undertaken for a number of years, and a number of purpose-specific septal occluders have been marketed. Recent randomised control trials have demonstrated that closure of PFO in patients with cryptogenic stroke is associated with reduced rates of recurrent stroke. After a brief overview of the anatomy of a PFO, this article considers the evidence for PFO closure in cryptogenic stroke. The article also addresses other potential indications for closure, including systemic arterial embolisation, decompression sickness, platypnoea–orthodeoxia syndrome and migraine with aura. The article lays out the pre-procedural investigations and preparation for the procedure. Finally, the article gives an overview of the procedure itself, including discussion of closure devices.